2015
DOI: 10.1136/injuryprev-2014-041419
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering a missing demographic in trauma registries: epidemiology of trauma among American Indians and Alaska Natives in Washington State

Abstract: Background The objectives of this study were to evaluate racial misclassification in a statewide trauma registry and to describe the epidemiology of trauma among the Washington American Indian and Alaska Native (AI/AN) population. Methods We performed probabilistic record linkage between the Washington Trauma Registry (2005–2009) and Northwest Tribal Registry, a dataset of known AI/AN. AI/AN patients were compared with caucasians on demographic, injury and clinical outcome factors. A multivariable model esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A total of 27 of the 66 (2%) articles met the criteria for the Dissemination domain. 5 , 7 , 33 , 40 , 41 , 47 , 49 , 51 , 53 , 56 , 60 , 61 , 67–69 , 73–76 , 78 , 85 , 86 , 88–90 , 97 , 98 These articles stated the relevance of the findings to relevant Indigenous governing bodies and peoples and/or implementation strategies. A total of 9 of the 66 (1.5%) articles met the criteria for the Participation domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 27 of the 66 (2%) articles met the criteria for the Dissemination domain. 5 , 7 , 33 , 40 , 41 , 47 , 49 , 51 , 53 , 56 , 60 , 61 , 67–69 , 73–76 , 78 , 85 , 86 , 88–90 , 97 , 98 These articles stated the relevance of the findings to relevant Indigenous governing bodies and peoples and/or implementation strategies. A total of 9 of the 66 (1.5%) articles met the criteria for the Participation domain.…”
Section: Resultsmentioning
confidence: 99%
“… 95 , 98 There were 10 (18%) articles that solely analyzed AI/AN populations and did not compare any other racial or ethnic group. 33 , 39 , 47 , 53 , 60 , 61 , 63 , 86 , 87 , 89 The most common method of addressing racial misclassification among these articles was linkage with the IHS or tribal clinic records (45 articles or 82%), linkage with tribal registries (4 articles or 7%), or tribal rolls (1 article or 2%). Two of the remaining five articles limited their analysis to counties served by the IHS and counties adjacent to reservation or Indian lands, 45 , 52 also known as Purchased/Referred Care Delivery Area (PRCDA), historically referenced as Contract Health Service Delivery Areas.…”
Section: Resultsmentioning
confidence: 99%
“…All-cause trauma is a major contributor to death within the indigenous populations of North America. 18 Population-wide studies of mortality indicate that indigenous people have the highest mortality rate within the following demographic categories: race/ethnicity, falls, and MVAs. 3 Similarly, Dudley et al 12 discuss the indigenous population of Quebec reported a rate of TBI of four times the general Canadian population.…”
Section: Discussionmentioning
confidence: 99%
“…leading to an underestimation of the burden of disease. [3][4][5][6] A large subset of the AI/AN population is served by the Indian Health Service (IHS), an integrated national health care delivery system of primarily rural clinics and hospitals. The IHS serves an estimated 2.2 million AI/ANs.…”
mentioning
confidence: 99%
“…2 However, because of a lack of complete and accurate data on race/ethnicity in national surveillance and vital statistics systems, it is often difficult to accurately assess the health status for this population, as AI/ANs are more likely to be misclassified as another race than are people from other racial/ethnic minority groups, leading to an underestimation of the burden of disease. 3 -6 A large subset of the AI/AN population is served by the Indian Health Service (IHS), an integrated national health care delivery system of primarily rural clinics and hospitals. The IHS serves an estimated 2.2 million AI/ANs.…”
mentioning
confidence: 99%